Da'wah and Religious Freedom: Study of the Hadiths of the Prophet's Da'wah to Non-Muslims - Akhsa Alpar Mubarok; Endad Musaddad (Aslama: Journal of Islamic Studies, 2025)
This article explores the concept of religious freedom in the context of Prophet Muhammad’s (peace be upon him) da'wah (Islamic preaching) to non-Muslims, focusing on a textual analysis of relevant hadiths. Using a qualitative approach and library research method, the study examines how the Prophet conveyed the message of Islam in a humane, persuasive, and non-coercive manner, as reflected in the Qur’anic principle lā ikrāha fī al-dīn (there is no compulsion in religion). The findings show that the Prophet’s da'wah was not merely aimed at conversion, but also at fostering just and harmonious interfaith relations. Concrete examples include his letter to Heraclius, the commissioning of Mu’adh ibn Jabal to Yemen, and hadiths emphasizing justice toward non-Muslims. This study affirms that religious freedom is an integral part of Islamic teachings and the prophetic tradition of da'wah. Hence, the article contributes to the discourse on a moderate, tolerant, and human rights-oriented approach to Islamic preaching.